Лексические инновации в мемосфере: названия мемных жанров - Makarowska, Olga (Studia Rossica Posnaniensia, 2020)
The development of the Internet gave life to Internet memes. Their diversity and rapid growth contributed to the formation of the memosphere, the development of which is accompanied by the emergence of lexical innovations. These include language memes and the names of meme genres. All of them are the result of linguistic creativity, which in relation to the names of meme genres, covers several stages: English loanwords for the name of the meme genre, their adaptation in Russian, changes in semantics, and preference for specific neologisms. The concept of lexical innovation was apprehended on the foundation of Markovsky’s concept. The study of lexical innovations was carried out within the framework of the structural-semantic direction, as well as on the basis of the theory of Kotelova and the concepts of Rakhmanova and Suzdaltseva. Studies have shown that semantic changes in the names of meme genres are associated with a denotation change. Changes in the semantics of word loaning are very dynamic as English loanwords enable the swift naming of new realities. This tendency towards the internationalization of vocabulary is related to the Internet and the memosphere. The obtained results fill the gap in the study of vocabulary related to the memosphere. A few studies of meme genres relate to their description and analysis, yet do not focus on the semantic and graphic modification of loanwords. This work presents the unprecedented mechanisms and stages of the formation of meme genres names.